2013
DOI: 10.1080/17405904.2013.813774
|View full text |Cite
|
Sign up to set email alerts
|

The ideologies behind newspaper crime reports of Latinos and Wall Street/CEOs: a critical analysis of metonymy in text and image

Abstract: The ideologies behind newspaper crime reports of Latinos and The ideologies behind newspaper crime reports of Latinos and Wall Street/CEOs: A critical analysis of metonymy in text and Wall Street/CEOs: A critical analysis of metonymy in text and image image

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 20 publications
0
21
0
Order By: Relevance
“…"Frequently, then, the truly powerless, rather than the truly evil, are demonized and stigmatized in the popular media" (Greer and Jewkes 2005, 29). A good example of research that examines how the wealthy and powerful are represented positively while minority groups and those without power are represented negatively in discourse about crime can be seen in Catalano and Waugh (2013). In this study, the authors found that Latino migrants were represented negatively in media discourse while CEOs convicted of heinous crimes were represented positively and in non-crime frames.…”
Section: Crime Media and Teachersmentioning
confidence: 73%
“…"Frequently, then, the truly powerless, rather than the truly evil, are demonized and stigmatized in the popular media" (Greer and Jewkes 2005, 29). A good example of research that examines how the wealthy and powerful are represented positively while minority groups and those without power are represented negatively in discourse about crime can be seen in Catalano and Waugh (2013). In this study, the authors found that Latino migrants were represented negatively in media discourse while CEOs convicted of heinous crimes were represented positively and in non-crime frames.…”
Section: Crime Media and Teachersmentioning
confidence: 73%
“…These comprise pragmatic strategies, discourse patterns and specific linguistic means such as metaphors and metonymies to reproduce stereotypes, ideologies, prejudice and identities (Catalano & Waugh, 2013; van Dijk, 2001;Horvat, Verschueren, & Žagar, 2001;Kazharsky, 2013;Kozlov, 2012;Le, 2006;Sowińska & Dubrovskaya, 2012b inter alios). Studies on the techniques of discursive construction of international relations also cover such discursive mechanisms as lexical construction of meanings (e.g.…”
Section: International Relations and Discourse Analysis: Literature Rmentioning
confidence: 98%
“…The results of their research showed that the social and psychological dimensions of CCA guide teachers in addressing how the social context of language and culture affect interactions with representatives from different cultures. According to K. Nugent and T. Catalano, critical cultural awareness should be treated as an expansion of intercultural communicative competence and must become an important part of the foreign language classroom [11]. This attitude helps students to deeper penetrate into the problem of understanding differences and common features of different cultures thus solving effectively the problem of connecting classrooms to real situations of global community.…”
Section: себя две теоретические дисциплины («межкультурная и поликульmentioning
confidence: 99%
“…Inside the theory of intercultural communicative competence some scientists started to speak about enhancing the role of cultural critical awareness -CCA -while teaching foreign languages (M. Byrom [7,8], K. Nugent and T. Catalano [11] and others). The results of their research showed that the social and psychological dimensions of CCA guide teachers in addressing how the social context of language and culture affect interactions with representatives from different cultures.…”
Section: себя две теоретические дисциплины («межкультурная и поликульmentioning
confidence: 99%